Application of A Decision Support System on Additive Ratio Assessment (ARAS) Method in Determining Best-Selling Korean Snacks - S Susliansyah; Heny Sumarno; Hendro Priyon; Linda Maulida; Fintri Indriyani (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
Nikmat group is a franchise company engaged in food and one of the brands owned by the company is GILDAK. GILDAK is a Korean snack business whose branches are everywhere. The different problem faced by each GILDAK branch located in each city is not being able to determine which snack menus are the most sold because consumers' tastes are different in each city, thus causing the franchisee to be inaccurate in determining what raw materials to use. in stock a lot, so as not to cause raw materials to run out. The Decision Support System (DSS) method that will be used in problem solving to determine the best-selling Korean service is the Additive Ratio Assessment (ARAS) method which has six stages such as determining the decision matrix, determining normalization, determining weights, determining normalized matrices, determining the value of the function. optimization and the highest ranking level. The results obtained from these calculations can be seen in the 5th stage, namely the best-selling snacks are Itaewon crispy chicken snacks ranked first with a value of 0.07783 (K1), original corndog snacks ranked second with a value of 0.07426 (K12) and gimpo snacks ranked third. with a value of 0.06907 (K9). It can be said that this method can be applied by companies in decision making.